The Effect of Supportive Psychotherapy Ventilation Techniques on Blood Pressure and Pulse rate in Depressed and Anxious Patients - Edy H. Mujahid; Erlyn Limoa (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Rates of depression and anxiety disorders are increasing worldwide. Anxiety and depression are one of the comorbidities of cardiovascular disease, cardiovascular conditions are worse with no comorbid depression and anxiety. Depression and anxiety are independent risk factors for hypertension. Previous studies involving groups of patients who received psychotherapy were found to have decreased blood pressure. Objective: To determine the effect of Ventilation Technique Supportive Psychotherapy on Blood Pressure (BP) and Pulse Rate in Depressed and Anxious Patients. Methods: Experimental research with a pre-test, post-test design was conducted at dr.Wahidin Sudirohusdo Makassar General Hospital and its network in May - July 2020. The samples of this study were patients with depressive disorders and anxiety disorders who underwent routine treatment as many as 12 samples and 12 controls. The research subjects were measured with the Hamilton Anxiety Rating Scale (HARS) and Hamilton Depression Rating Scale (HDRS) and then checked blood pressure and pulse rate before and after the subject was given psychotherapy for 30 minutes. Data were analyzed using Pearson test. Results: The total sample was 12 treatment and 12 control people with an average age of 45.8. Statistically significant changes in systole blood pressure, diastole blood pressure and pulse rate were obtained before and after the provision of supportive psychotherapy ventilation techniques with a significant p value (p < 0.001). Based on the Pearson correlation test, the comparison of systole blood pressure, diastole blood pressure and pulse rate of the two groups was significant and the correlation was very strong (0.938) in systole blood pressure and (0.908) in diastole blood pressure and a strong correlation (0.729) in pulse rate. Conclusion: There was a significant reduction in systole blood pressure, diastole and pulse rate in the treatment group after receiving Ventilation Technique Supportive Psychotherapy when compared to the control.